Structural and Functional Features of Peyer's Plates in the Formation of the Immune System of the Small Intestinal (Literature Review) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
The article is devoted to a review of foreign literature on the structure and functioning of Peyer's patches. The lymphoid system located in the intestinal wall, associated with the mucous membrane, ensures the development of an immune response in response to the penetration of pathogenic agents and provides immunological tolerance towards food components and commensal bacteria.